Household Economic Capacity for Sustainable Oil Palm Replanting Costs - Livia Vinota; Maryadi; Agustina Bidarti (Institut Pertanian Bogor, 2026)
Oil palms have significant growth potential owing to their favorable prospects in domestic and international markets, serving as a primary source of income for local communities. As oil palm farming serves as the main source of income for local communities, its sustainability must be ensured. However, there are challenges, notably the declining production of oil palm crops as plantations reach a certain age. To address this, the government launched the People’s Oil Palm Replanting Program (PSR), aimed at improving the efficiency and effectiveness of managing oil palm farming activities. However, the high costs associated with replanting often impose financial burdens on farmers. This study proposes an income set-aside system for smallholder farmers during the productive life of their plantations to alleviate the financial burden of replanting the palms. This article discusses the calculation of farmers’ remaining household income and the amount of savings they need to accumulate funds for oil palm replanting activities. The data were quantitatively processed, including calculations of household income, expenditures, and remaining household income, and the value of savings for oil palm replanting preparation using the Sinking Fund Factor method. The study results revealed that most oil palm farmers (72%) have a sufficient amount of remaining household income that can be set aside as savings to prepare funds for oil palm replanting. Farmers need to allocate only 6.07% of their total household income, equivalent to IDR 678,165 per plantation area per month, to save for replanting oil palms. Keywords: farmers’ savings, oil palm farming, replanting fund